The social value generated by sheltered workshops in Spain: comparison of two monetization approaches - Ayuso Siart, Silvia (REVESCO. Revista de Estudios Cooperativos, 2023)
Sheltered workshops are social economy companies that reconcile participation in the market and economic viability with the social function of integrating people with disabilities. The aim of this paper is to compare two approaches used to analyze the social value generated by sheltered workshops in monetary terms: the Social Return on Investment (SROI) and the Integrated Social Value (ISV). Based on a review of eleven case studies of Spanish sheltered workshops, the scope of the studies, the identified stakeholders, the value categories considered and the process of monetizing them are explored. The comparative analysis of the SROI and ISV studies concludes that the two methodologies show many similarities in the social value measurement process, but also some significant differences that influence the amounts calculated.